Growth of Teak (Tectona grandis Linn. f) Stumps in Bagasse Fly Ash Incorporated Medium - Masilamani, P.; Balasubramaniam, P.; Alex Albert, V.; Govindaraj, M. (Indian Forester, 2019)
Seedling growth performance of Tectona grandis stumps were evaluated in a range of growth media with and without bagasse fly ash as a component. The results revealed that after thirty days of planting the stumps in nursery media, the maximum survival (98%) was observed in stumps planted in red earth + sand + farm yard manure at 2:1:1 ratio followed by 90 per cent survival in stumps planted in fly ash + red earth + farm yard manure at 1:1:1 ratio. The observation on number of leaves per stump, number of secondary roots per stump and dry matter production were highest i.e., 6.0, 6.3, 3.67 at the stumps planted in red earth alone. The results for sixty days after planting observation on survival percentage, shoot length, number of leaves per stump, number of secondary roots per stump and dry matter production were also highest 10.0, 8.0 and 6. 30 in stumps planted in fly ash + sand + farm yard manure at 1:1:1 ratio. Hence, the present investigations concluded that among the different media evaluated for seedling growth, bagasse fly ash mixed with sand and farm yard manure at 1:1:1 ratio found to be the best in terms of survival and initial seedling growth in Tectona grandis.